Kajian Peningkatan Kapasitas PLTA Lodoyo - Widyaningsih, Wiwik; Rispiningtati, Rispiningtati; Juwono, Pitojo Tri (Fakultas Teknik, Universitas Brawijaya, 2012)
Lodoyo dam has the potential to development of energy resources especially hydro energy power plant (HEPP), where the excess outflow discharge through spillway still have potential for capacity improvement.With the availability of outflow discharge through spillway data, the additional potential energy can be calculated, by analyze of head effective and energy. Also can performed in economic feasibility with parameter B/C Ratio, IRR, and NPV where benefit value calculated from the selling price of electric generated. The optimum improvement based on four alternative discharge outflow design with two alternative alignment. From 1st alternative analysis where located on the left river, the largest value of B/C Ratio at 1.037 (at the rate 12%) on discharge outflow at 34.05 m3/sec (Q75%) with an installed capacity 3.20 MW, and an annual energy at 25.58 GWh. For 2nd alternative where located on the right side of river has largest B/C Ratio values at 1.076 on the same discharge outflow with an annual energy of 25,65 GWh so this alternative has the most optimal of potential energy.Key words: discharge, head, energy, economic feasibility.